Contralateral pharyngeal paralysis caused by medial medullary infarction. Issue 9 (16th August 2005) - Nakajima, M; Inoue, M; Sakai, Y
Abstract : A patient with unilateral upper medial medullary infarction presented with contralateral paralysis of the pharyngeal constrictor muscle in association with lemniscal sensory loss, pyramidal insufficiency, and central facial palsy on the same side. Individual differences in supranuclear control of the pharyngeal muscles may explain this rare occurrence. The combination of these signs is described as a syndrome of upper medial medullary lesion.